Mary: Icon of Grace - Huijgen, Arnold (Verbum Christi: Journal of Reformed Evangelical Theology, 2023)
The article's focus is the way a theological appreciation of Mary can enrich Reformed theology. I will argue that it can do so in the following three ways: (1) Mary is a prime example of faith, an ideal servant of the Lord, and in a sense the mother of all believers; (2) Mary reminds us of God’s faithfulness to the Jewish people, and wards off gnostic heresies; (3) Mary is a symbol of Christianity that has often been misused, but can be put to a good use, and reflection on Mary helps to steer clear of one-sided approaches of the position of women and furthers Reformed reflection on gender. The discussion of each of these aspects is based on exegesis of a passage of Scripture, and considers an aspect of the theological tradition.
Keywords: Mary; Mariology; Reformed Theology